Translating imperative mood in the glorious Qur’an into English - Fathi, Dhuha Abduljabbar (2017)
Much ink has been spilt on the study of imperative mood in Arabic. No doubt, languages of humankind have many semantic notions to share with other languages. It is a matter of fact that Arabic is a flexible language in the sense that it has a variety of linguistic devices that it expresses different types of meaning. Among these types are speaker’s attitudes toward the action (Mood). Mood as a semantic notion has different sets, among which is the imperative mood (the subject matter of the present study). Hence, the problem arises. In addition, the language of the Glorious Qur'an is sacred and considered as a classical language, which increases the problem of transferring these verses from Arabic into English. Furthermore, the interpretation of the Glorious Qur’an is sometimes different from one interpreter to another one, which means that the translator will be perplexed and does not know which interpretation to follow, for example Zamakhshari (1407H), Al-Qurtuby (2008), Qutub (1980), As- Saboony (1981), al-Jalalayn (1280 ah.), and Ibn Kathir (1969). Throughout this study, the purpose of this study in general, attempts to identify and explain the translation of imperative mood in Glorious Qur'an into English. This study incorporates other primary aims: First, identifying the translation of imperative mood in the Glorious Quran from Arabic into English as translated by the selected translators. Secondly, analyzing the method of translation that was followed in rendering the imperative mood by the selected translators, and determine the extent to which the four translators maintained the same pragmatic functions of the imperative mood in their translations of the Glorious Quran into English. Due to the complexity of imperative mood system in Arabic, it is hypothesized that effective rendering can be produced only if transference of meaning is made. The findings of this thesis showed that all of the translators relied heavily on using semantic translation in rendering imperative mood. In addition, most of translators used different lexicons to express the imperative verb in English. Besides, they followed a communicative translation whenever they believed that the functions of the imperative mood in verses are ambiguous. Conclusion, implications, directions for further studies, and some recommendations for pedagogical implications were provided at the end of the thesis.